Blasting Energy Analysis of the Different Cutting Methods. (16th December 2018) - Man, Ke; Liu, Xiaoli; Wang, Ju; Wang, Xiyong
Abstract : Based on the smooth blasting method, the blasting parameters of the Beishan exploration tunnel have been designed. According to the principle of blasting parameters design, three kinds of cutting methods have been laid out, which are straight parallel hole cutting, single-wedge cutting, and double-wedge cutting. The other parameters such as the borehole number, the detonator segment, and the charge amount of each hole are also designed. Then, the blasting tests under different cutting methods were carried out in the field. The results show that all the three cutting methods can achieve good utilization ratio of blasting holes. The blasting effect of straight parallel hole cutting is good. The rock slag size of single-wedge and double-wedge cutting is uniform, which is beneficial to slag extraction. Moreover, the blasting vibration velocity and blasting energy have been analyzed. It is found that the energy distribution of single-wedge and double-wedge cutting is more uniform, mainly concentrated in the high-frequency part, while the energy of straight parallel hole cutting is more concentrated in the low-frequency part. Among many factors affecting blasting vibration velocity, besides the explosive quantity, it would also be easily influenced by the cutting way. It should be noticed that the blasting method includes numerous blasting parameters, which interact with each other. Those blasting parameters obtained were just limited to the cutting method, and the result and the theoretical knowledge could be applied to the blasting and excavation of the deep geoengineering and the HLW geo-disposal.